Effectiveness of sulfuric acid and hydrochloric acid catalysts in the esterification of frankincense cinnamic acid with ethanol and methanol - Sitorus, Marham; Suyanti, Retno Dwi; Jahro, Iis Siti; Siahaan, Suria Bersinar; Saragih, Innovayani; Sitorus, Francisca T. A (Pascasarjana Universitas Negeri Medan, 2024)
This research aims to compare the effectiveness of sulfuric acid and hydrochloric acid catalysts in the esterification of frankincense cinnamic acid (STYRAX paraleoncomud PERK). Esterification of sulfuric acid catalyst is carried out with ethanol and for hydrochloric acid catalyst with methanol. Esterification was carried out by refluxing a mixture of 1:20 cinnamic acid - ethanol and methanol, with 3 mL of each catalyst at a temperature of 60oC for one hour. The results were rinsed with 3 x 50 mL distilled water and dried with anhydrous sodium sulfate. The results were filtered and verified for functional groups using FTIR and composition analysis using GC “ MS. The results of FTIR interpretation show a decrease in absorption intensity (-OH) at 3500 cm-1 as a functional group that reacts compared to the ester results as an indication of the ongoing esterification reaction. The resulting ethyl cinnamate has a high conversion of 84.42%. Methyl cinnamate also has a distinctive ester aroma but is clearer and based on GC-MS, the content of methyl cinnamate is relatively low, namely 34.40%, the remaining cinnamic acid is 37.28%, and various side products of 28.32%. Thus, the catalyst that provides better conversion is sulfuric acid, but it requires further purification by examining the appropriate absorbent and bleaching agent. The brown color of the ester product catalyzed by sulfuric acid is thought to occur due to the oxidation of the cinnamic acid double bond by the catalyst.